Adductor canal block versus local infiltration analgesia for postoperative pain after anterior cruciate ligament reconstruction: a single centre randomised controlled triple-blinded trial. (August 2019) - Stebler, Kevin; Martin, Robin; Kirkham, Kyle R.; Lambert, Jean; De Sede, Anne; Albrecht, Eric
Abstract: Background: Both the adductor canal block (ACB) and local infiltration analgesia (LIA) are effective analgesic techniques after anterior cruciate ligament (ACL) reconstruction, but they have never been compared head-to-head. This randomised controlled triple-blinded trial tested the hypothesis that ACB provides superior analgesia to LIA after ACL reconstruction, with additional focus on postoperative functional outcomes. Methods: Of 104 enrolled ACL reconstruction patients receiving general anaesthesia, 52 were randomly allocated to either ACB under ultrasound guidance or LIA. For each intervention, ropivacaine 0.5%, 20 ml was injected. Postoperative pain treatment followed a predefined protocol with i.v. patient-controlled morphine, paracetamol, and ibuprofen. The primary outcome was cumulative i.v. morphine consumption at 24 h after operation. Secondary pain-related outcomes included resting and dynamic pain scores (numeric rating scale out of 10) measured 2, 24, and 48 h after operation and cumulative i.v. morphine consumption 2 and 48 h after operation. Early function-related outcomes evaluated were quadriceps strength, walking distance, and range of motion, all measured 24 and 48 h after operation. Late function-related outcomes were concentric quadriceps strength, single-hop test, triple-hop test, cross-over test, and Y balance test, measured at 4 and 8 postoperative months. Results: Cumulative i.v. morphine consumption at 24 h was similar between groups (ACB group: 17.1 mg [95% confidence interval, CI: 13.1, 21.2]; LIA group: 17.7 mg [95% CI: 13.2, 22.6], P =0.84). Similarly, no differences between groups were seen in the secondary pain- or function-related outcomes. Conclusions: ACB and LIA result in equivalent postoperative opioid consumption with similar impact on postoperative pain scores and functional outcomes. Clinical trial registration: NCT 02524652.